Age-Related Changes in Skeletal Muscle Iron Homeostasis. Issue 1 (23rd July 2022) - Alves, Francesca M; Ayton, Scott; Bush, Ashley I; Lynch, Gordon S; Koopman, René
Abstract: Sarcopenia is an age-related condition of slow, progressive loss of muscle mass and strength, which contributes to frailty, increased risk of hospitalization and mortality, and increased health care costs. The incidence of sarcopenia is predicted to increase to >200 million affected older adults worldwide over the next 40 years, highlighting the urgency for understanding biological mechanisms and developing effective interventions. An understanding of the mechanisms underlying sarcopenia remains incomplete. Iron in the muscle is important for various metabolic functions, including oxygen supply and electron transfer during energy production, yet these same chemical properties of iron may be deleterious to the muscle when either in excess or when biochemically unshackled (eg, in ferroptosis), it can promote oxidative stress and induce inflammation. This review outlines the mechanisms leading to iron overload in muscle with aging and evaluates the evidence for the iron overload hypothesis of sarcopenia. Based on current evidence, studies are needed to (a) determine the mechanisms leading to iron overload in skeletal muscle during aging; and (b) investigate whether skeletal muscles are functionally deficient in iron during aging leading to impairments in oxidative metabolism. Graphical Abstract: